Dietary Fiber Intake and Femoral Bone Mineral Density in Middle-Aged and Older US Adults: A Cross-Sectional Study of National Health and Nutrition Examination Survey 2013–2014 - Tang, Yuchen; Liu, Jinmin; Zhang, Xiaohui; Geng, Bin (Frontiers in Nutrition, 2022)
Sufficient dietary fiber intake (DFI) is considered necessary for human health. However, the association between DFI and bone mineral density (BMD) remains unclear. Therefore, this study aimed to investigate the association between DFI and BMD and to determine whether sex modifies the association between DFI and BMD. Participants aged ≥ 40 years from the 2013–2014 National Health and Nutrition Examination Survey were included in the final analysis. The association between DFI and BMD was evaluated using a multivariate linear regression model. The non-linear relationship between DFI and BMD was characterized by smooth curve fittings and generalized additive models. Finally, 1,935 participants with a mean age of 58.12 ± 11.84 years were included in the final analysis. The results revealed that DFI was positively associated with femoral BMD in the unadjusted model. However, no correlation was observed between DFI and femoral BMD after adjusting for covariates. Moreover, the results showed an inverted U-shaped association between total DFI and femoral BMD among men but not women for the nonlinear relationship between DFI and femoral BMD. In conclusion, our results indicate that DFI might not follow a linear relationship with femoral BMD, and sex factors might modify the association between DFI and BMD. Particularly, high total DFI might contribute to lower femoral neck BMD. However, more studies are needed to investigate whether the negative effect of high DFI on femoral BMD does exist and whether high DFI has clear biological effects on bone metabolism, such as increasing the risk of osteoporosis.